Atypical brain functional segregation is more frequent in situs inversus totalis. (September 2018) - Vingerhoets, Guy; Gerrits, Robin; Bogaert, Stephanie
Abstract: Most humans show typical brain functional specialization with language and praxis favoring left hemisphere lateralization and spatial attention and face recognition showing right hemisphere dominance. Lateralization of these cognitive functions was investigated using fMRI in participants with complete visceral reversal and matched control participants. While most participants revealed typical brain organization, atypical functional segregation was significantly more frequent in participants with visceral reversal. Interestingly, some left handers maintained typical functional segregation but showed complete reversal of all cognitive functions regardless of visceral organization. Cognitive performance, as measured with a neuropsychological test battery, was significantly predicted by the degree of atypical functional segregation of praxis and spatial attention. Increased deviation from typical functional segregation paired with lower cognitive performance. The findings suggest that typical functional segregation reflects an optimal evolutionary solution with deviations being associated with reduced cognitive performance.